Kontrowersje wokół zbiegu przepisów art. 86 § 2 i 87 k.w. - Szwarc, Andrzej (Wydział Prawa i Administracji UAM, 1987)
Controversies around the concurrence of Art. 86 § 2 and 87 of Petty Offences' Code (POC) appeared after the modifications of those provisions have been introduced by the law of May 10, 1985 The doubts were concerned with legal qualification and the measure of penalty in cases when an offender drives a vehicle after he has consumed alcohol or some other substances causing similar effects and, acting carelessly, ne brings about a threat to traffic The author shares an opinion that in such a case there is a so-called real consurence of offences described in Art 86 § 2 and 87 § 1 or 2 of POC and that in the above conditions the directives formulated in Art 9 § 1 of POC should be applied Contrary to different views, the author is of the opinion that according to those directives, in the event of the concurrence of Art 86 § 2 and 87 § 1 of POC the main penalty should be meted out on the basis of Art. 86 § 2 whereas the additional penalty — i.e. the interdiction to drive vehicles — on the basis of Art. 87 § 3 of POC.
Controversies around the concurrence of provisions of Art. 86 § 2 and 87 of Petty Offences Code